Temperature dependence of evolutionary diversification: differences between two contrasting model taxa support the metabolic theory of ecology - Machac, A; Zrzavý, J; Smrckova, J; Storch, D (Journal of evolutionary biology, 2012)
Biodiversity patterns are largely determined by variation of diversification rates across clades and geographic regions. Although there are multiple reasons for this variation, it has been hypothesized that metabolic rate is the crucial driver of diversification of evolutionary lineages. According to the metabolic theory of ecology (MTE), metabolic rate - and consequently speciation - is driven mainly by body size and environmental temperature. As environmental temperature affects metabolic rate in ecto- and endotherms differently, its impact on diversification rate should also differ between the two types of organisms. Employing two independent approaches, we analysed correlates of speciation rates and, ultimately, net diversification rates for two contrasting taxa: plethodontid salamanders and carnivoran mammals. Whereas in the ectothermic plethodontids speciation rates positively correlated with environmental temperature, in the endothermic carnivorans a reverse, negative correlation was detected. These findings comply with predictions of the MTE and suggest that similar geographic patterns of biodiversity across taxa (e.g. ecto- and endotherms) might have been generated by different ecological and evolutionary processes.
Keywords: ekologie; modely genetické; vznik druhů (genetika); velikost těla; Urodela; Animals; Phylogeny; Temperature; Ecology; Models, Genetic; zvířata; Body Size; fylogeneze; teplota; Genetic Speciation; Caudata